Análisis de los factores de riesgo: seguridad industrial, salud ocupacional e infraestructura de la Cooperativa de Ahorro y Crédito Cacpe-Celica y la propuesta de un plan de mejora - Luis Daniel, Granda García (2016)
This thesis develops a plan of industrial safety and occupational health and improving its infrastructure, based on the Management System for Safety and Health at Work, the Ecuadorian Institute of Social Security in order to change the existing organizational culture in credit union where CELICA CACPE-develop the plan, ie, form a subsystem exert considerable influence on its rules, values, ideas and institutional beliefs, by which they will face internal challenges of the institution. The first part sets out the objectives, methodology and structure of the thesis will then review all the theoretical foundations necessary to consider in preparing the plan and infrastructure such as basic definitions of industrial safety and occupational health and infrastructure, System explanation Management of Health and Safety at Work's Social Security Institute, learning principles, importance of communication and implications of organizational culture change. After briefly describes the facility where the program will be developed, analyzed the system of industrial safety and identify areas where risks. Then the plan is designed for industrial safety and occupational health and infrastructure, based on the Management System for Safety and Health at Work of the Social Security Institute previously explaining levels to comply within a plan and the important elements to consolidate . Finally establishes the evaluation and monitoring of the plan and its infrastructure and get the conclusions and recommendations of the work.